Pengaruh Kualitas Kepemimpinan Terhadap Motivasi Kerja Pegawai (Studi Kasus di Desa Bongas Kecamatan Cililin) - Fitra Ramandayani; Fizi Fauziya (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Employees are an essential part of an organization and the main driving force behind its operations. The success or failure of an organization will affect the achievement of its goals. One indicator of an organization's success is the work motivation of its employees. Every employee needs a quality leader who can foster high work motivation, allowing employees to work in a more focused manner and the organization's goals can be easily achieved. This study aims to determine the influence of leadership quality on employee work motivation in Bongas Village, Cililin District. The type of research used is descriptive research, with a quantitative approach. The sampling technique used is simple random sampling with a sample size of 36 employees in Bongas Village. Data was obtained by distributing questionnaires. This study uses simple linear regression analysis with the help of SPSS 27.0 software. The results of the study show that leadership quality has a positive and significant influence on employee work motivation in Bongas Village. This can be seen from the regression coefficient value of 0.919, the correlation coefficient of 0.889, and the coefficient of determination of 0.791, which shows that leadership quality influences work motivation by 79.1%, while the rest is influenced by other variables.